Implementasi Nation Branding Korea Selatan Melalui Esports Tahun 2003-2014 - RACHMADANA, TAZSYAQI DENIV (Global and Policy Journal of International Relations, 2024)
South Korea is one of the countries in the world that has become a driving force in the development of the gaming world. Starting in 2003, the gaming industry in South Korea began to develop significantly by focusing on promoting domestic games and developing them in foreign markets. To strengthen South Korea's promotion in the eSports sector in the following years, several nation branding efforts were implemented, including strategy, substance and symbolic action. Strategy is carried out through policy making and medium and long term planning which has been created to outline the goals and direction of planning used to promote the South Korean gaming and eSports industry. Substance is carried out through holding various national and international competitions, participation in international exhibitions, holding eSports cultural festivals, holding international gaming conferences and holding international eSports Symposiums. Symbolic action is carried out through holding international game exhibitions and eSports competitions, both national and international competitions with the aim of achieving status as an eSports leader and becoming a leader in the gaming industry sector so that South Korea's nation branding as an eSports country is formed.Keywords: South Korea, eSports, nation brandingKorea Selatan merupakan salah satu negara didunia yang telah menjadi kekuatan pendorong dalam perkembangan dunia game. Diawali pada tahun 2003, dimana industri game di Korea Selatan mulai berkembang secara signifikan dengan berfokus pada promosi game dalam negeri dan pengembangannya dalam pasar luar negeri. Untuk menguatkan promosi Korea Selatan dalam bidang eSports ditahun-tahun berikutnya dilakukanlah beberapa implementasi upaya – upaya nation branding antara lain strategy, substance, dan symbolic action. Strategy dilakukan melalui pembuatan kebijakan dan perencanaan jangka menengah dan jangka panjang yang telah dibuat untuk menguraikan tujuan serta arah perencanaan yang digunakan untuk mempromosikan industri game dan eSports Korea Selatan. Substance dilakukan melalui penyelenggaraan berbagai Kompetisi nasional maupun internasional, partisipasi dalam pameran internasional, pengadaan festival budaya eSports, pengadaan Konferensi game internasional dan pengadaan Simposium eSports internasional. Symbolic action dilakukan melalui penyelenggaraan pameran game internasional dan KompetisiKompetisi eSports baik kompetisi nasional dan internasional dengan tujuan untuk mencapai status sebagai pemimpin eSports serta menjadi Pemimpin di sektor industri game sehingga terbentuk nation branding Korea Selatan sebagai negara eSports.Kata Kunci: Korea Selatan, eSports, nation brandingDOI: https://doi.org/10.33005/jgp.v12i01.4313